Controlling the shape of 3D microstructures by temperature and light - Hippler, Marc; Tanaka, Motomu (Nature Communications, 2019)
Stimuli-responsive microstructures are important in soft robotics and biosciences, but water compatible materials to fabricate 3D structures are scarce. Here, the authors demonstrate pNIPAM based hetero-microstructures with substantially different material parameters by variation of the local exposure dose in 3D laser lithography.